Biomaterials delivery strategies to repair degenerated intervertebral discs by regulating the inflammatory microenvironment - Xia, Yuanliang; Wang, Hengyi; Yang, Ruohan; Hou, Yulin; Li, Yuehong; Zhu, Jianshu; Fu, Changfeng (Frontiers in Immunology, 2023)
Intervertebral disc degeneration (IVDD) is one of the leading causes of lower back pain. Although IVDD cannot directly cause death, it can cause pain, psychological burdens, and economic burdens to patients. Current conservative treatments for IVDD can relieve pain but cannot reverse the disease. Patients who cannot tolerate pain usually resort to a strategy of surgical resection of the degenerated disc. However, the surgical removal of IVDD can affect the stability of adjacent discs. Furthermore, the probability of the reherniation of the intervertebral disc (IVD) after surgery is as high as 21.2%. Strategies based on tissue engineering to deliver stem cells for the regeneration of nucleus purposes (NP) and annulus fibrosus (AF) have been extensively studied. The developed biomaterials not only locally withstand the pressure of the IVD but also lay the foundation for the survival of stem cells. However, the structure of IVDs does not provide sufficient nutrients for delivered stem cells. The role of immune mechanisms in IVDD has recently become clear. In IVDD, the IVD that was originally in immune privilege prevents the attack of immune cells (mainly effector T cells and macrophages) and aggravates the disease. Immune regulatory and inflammatory factors released by effector T cells, macrophages, and the IVD further aggravate IVDD. Reversing IVDD by regulating the inflammatory microenvironment is a potential approach for the treatment of the disease. However, the biological factors modulating the inflammatory microenvironment easily degrade in vivo. It makes it possible for different biomaterials to modulate the inflammatory microenvironment to repair IVDD. In this review, we have discussed the structures of IVDs and the immune mechanisms underlying IVDD. We have described the immune mechanisms elicited by different biological factors, including tumor necrosis factors, interleukins, transforming growth factors, hypoxia-inducible factors, and reactive oxygen species in IVDs. Finally, we have discussed the biomaterials used to modulate the inflammatory microenvironment to repair IVDD and their development.